2018
DOI: 10.3389/fimmu.2018.02693
|View full text |Cite
|
Sign up to set email alerts
|

Pro-inflammatory Monocyte Phenotype and Cell-Specific Steroid Signaling Alterations in Unmedicated Patients With Major Depressive Disorder

Abstract: Several lines of evidence have strongly implicated inflammatory processes in the pathobiology of major depressive disorder (MDD). However, the cellular origin of inflammatory signals and their specificity remain unclear. We examined the phenotype and glucocorticoid signaling in key cell populations of the innate immune system (monocytes) vs. adaptive immunity (T cells) in a sample of 35 well-characterized, antidepressant-free patients with MDD and 35 healthy controls individually matched for age, sex, smoking … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 50 publications
3
25
2
Order By: Relevance
“…The differences in methodology and study populations may explain the observed discrepancies between earlier and current studies. Using a similar experimental methodology, our observations of the expansion and retraction of the intermediate monocytes and classical monocytes in MDD patients agree with recently published results (37). Furthermore, the percentage of nonclassical monocytes is normal in MDD patients.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The differences in methodology and study populations may explain the observed discrepancies between earlier and current studies. Using a similar experimental methodology, our observations of the expansion and retraction of the intermediate monocytes and classical monocytes in MDD patients agree with recently published results (37). Furthermore, the percentage of nonclassical monocytes is normal in MDD patients.…”
Section: Discussionsupporting
confidence: 91%
“…Conflicting results regarding the classical and nonclassical monocyte subset frequencies have been previously described in MDD patients (25, 28, 29, 37). The differences in methodology and study populations may explain the observed discrepancies between earlier and current studies.…”
Section: Discussionmentioning
confidence: 85%
“…1). Immune alterations, such as a reduction in the frequency of classical monocytes, and an increase in nonclassical monocytes [10], are hypothesized to be a result of neurotoxic processes occurring in response to stress in morphologically altered brains, mediated by dysregulation of the hypothalamic-pituitary-adrenal axis and a positive inflammation feedback loop [9 ▪▪ ]. Cell-mediated immune cytokines are increased, activating indoleamine 2,3-dioxygenase.…”
Section: Rationale For Depression As a Risk Factor For Rheumatoid Artmentioning
confidence: 99%
“…Depression has been reproducibly associated with leukocytosis, increased neutrophil-to-lymphocyte ratio, and increased ratio of CD4 1 to CD8 1 T cells (19)(20)(21). However, there are less consistent results concerning regulatory T cells, T-helper 17 cells, natural killer (NK) cells, monocytes, and B cells (12)(13)(14)(15)(16)18,22). Other psychiatric disorders, including schizophrenia, bipolar disorder, and autism, have also been associated with altered cell counts (23)(24)(25).…”
mentioning
confidence: 99%